Local Knowledge on Towards The Conservation of Macaca nigra in KPHK Tangkoko, North Sulawesi - Djafar, Sintia; Rampengan, Mercy; Yalindua, Aser (Indonesian Biodiversity Journal, 2024)
The Yaki monkey (Macaca nigra) is a critically endangered endemic species of North Sulawesi and is listed in Appendix II of CITES as well as in-situ conservation at the Tangkoko Conservation Forest Management Union (KPHK Tangkoko). The public's knowledge of the conservation of M. nigra is a key factor inining the sustainability of this species. The aim of this research is to find out the level of public awareness about conservation of M. nigra. This research uses descriptive methods. Data collection is done with a questionnaire with scored using the Guttman scale. The results of this study show that the majority of the level of knowledge in the community in the buffer zone KPHK Tangkoko belongs to a level of good, sufficient, and insufficient to the conservation status of m. nigra. Respondents who have good knowledge are all respondents in the Batu Putih Bawah villages and Duasudara villages. While the majority of the population in the Kasawari villages (63%) and the Pinangunian villages (68%) have sufficient knowledge about the conservation status of the M. nigra while almost half of the Kasawari villages (37%) and Pinangunian villages (32%) have insufficient knowledge.